Abundance, composition and distribution of phytoplankton in Verde Island passage - Formilleza, Jireh Joy T. (2008.)
Phytoplankton in Verde Island Passage were investigated from May 21-28, 2007. Samples were collected from 83 stations distributed widely over the study area by filtering 50 L of surface waters through a net with a 20 um mesh bag. Of these, 25 samples were exemined in this study. The phytoplankton consisted of four major groups. Diatoms showed the highest mean density of 2315 cells/L. Blue green algae comprised the most abundant group with a mean density of 1,251.5 cell/L. Dinoflagellate followed with a mean density of 84.4 cells/L, while the silicoflagellates had a mean density of 57.6 cells/L. The 3 most dominant diatoms were Chaetoceros, Bacteriastrum, and Rhizosolenia. The blue-green algae comprised only two genera, Trichodesmium and Richelia. Among the dinoflagellates, Prorocentrum was the most abundant, while Eutintinnus dominated the silicoflagellates. High phytoplankton concentration were observed in the middle portion of the passage which is the narrowest. Overall abundance in the study area may be attributed to factors acting on both large and local scales.
Special Problem (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo
Keywords: Phytoplankton -- Verde Island Passage